Torturing the helpless: A review of PCOS induced infertility from a gender perspective - Atijosan, Ayobami Basirat (Journal of Gender and Power, 2021)
This paper reviewed the abuse of infertile women suffering from Polycystic Ovary Syndrome (PCOS) from a gender perspective. Infertility is a prevalent, presenting feature of PCOS with 75% of women experiencing infertility due to anovulation, making PCOS the most common cause of anovulatory infertility. Increased awareness of PCOS, its causes, and its symptoms may help the process of early diagnosis, appropriate care and mitigation of violence arising from infertility hence, this study. In many countries’ infertility among married couples especially for women is a sentence to stigmatization, loss of social status, marital conflicts and violence. All this stems from prevailing socio-cultural norms and gender inequalities inimical to women. PCOS is a syndrome without much public awareness and PCOS patients often do not seek care. Where they seek care, they are often not immediately diagnosed with PCOS. Due to some prevailing cultural norms and general lack of awareness they are often tortured and abused. Outcomes from this study shows that there is need to intensify public awareness on the various factors contributing to infertility such as PCOS which has been identified as a major contributing factor. Also, harmful socio-cultural norms and practices that encourages gender inequalities and violence against infertile women should be eradicated with strong policies put in place and perpetrators severely punished. Early diagnosis and a multidisciplinary approach to the treatment of PCOS is also crucial. Finally, proactiveness by implementing working strategies that will help improve treatment and mitigate violence against women suffering from PCOS should be embrace by all.